Does C-Reactive Protein Contribute to Atherothrombosis Via Oxidant-Mediated Release of Pro-Thrombotic Factors and Activation of Platelets? - Zhang, Zhuo; Yang, Yan; Hill, Michael A.; Wu, Jianbo (Frontiers in Physiology, 2012)
Inflammation and the generation of reactive oxygen species (ROS) have been implicated in the initiation and progression of atherosclerosis. Although C-reactive protein (CRP) has traditionally been considered to be a biomarker of inflammation, recent in vitro and in vivo studies have provided evidence that CRP, itself, exerts pro-thrombotic effects on vascular cells and may thus play a critical role in the development of atherothrombosis. Of particular importance is that CRP interacts with Fcγ receptors on cells of the vascular wall giving rise to the release of pro-thrombotic factors. The present review focuses on distinct sources of CRP-mediated ROS generation as well as the pivotal role of ROS in CRP-induced tissue factor expression. These studies provide considerable insight into the role of the oxidative mechanisms in CRP-mediated stimulation of pro-thrombotic factors and activation of platelets. Collectively, the available data provide strong support for ROS playing an important intermediary role in the relationship between CRP and atherothrombosis.